2022
DOI: 10.3389/fmed.2022.854677
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Deep Neural Network for Accurate Identification of Endoscopic Images From Patients With Ulcerative Colitis and Crohn's Disease

Abstract: Background and AimThe identification of ulcerative colitis (UC) and Crohn's disease (CD) is a key element interfering with therapeutic response, but it is often difficult for less experienced endoscopists to identify UC and CD. Therefore, we aimed to develop and validate a deep learning diagnostic system trained on a large number of colonoscopy images to distinguish UC and CD.MethodsThis multicenter, diagnostic study was performed in 5 hospitals in China. Normal individuals and active patients with inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…For the UC-CD cases, we observed that classification metrics are not able to perfectly distinguish between the two, which is in line with what previous machine learning studies suggest. Indeed, among the different datasets and ML techniques used in the literature to diagnose UC vs CD, such as using RNA sequencing data [32] or endoscopic images [33], none has been able to perform as a perfect classifier. Additionally, we note that in the case of HC and NH, all the accuracies are relatively high for all methods, suggesting the strong capability of ML methods to distinguish between HC and NH.…”
Section: Resultsmentioning
confidence: 99%
“…For the UC-CD cases, we observed that classification metrics are not able to perfectly distinguish between the two, which is in line with what previous machine learning studies suggest. Indeed, among the different datasets and ML techniques used in the literature to diagnose UC vs CD, such as using RNA sequencing data [32] or endoscopic images [33], none has been able to perform as a perfect classifier. Additionally, we note that in the case of HC and NH, all the accuracies are relatively high for all methods, suggesting the strong capability of ML methods to distinguish between HC and NH.…”
Section: Resultsmentioning
confidence: 99%
“…ResNet, a more frequently used CNN architecture in IBD, has been used for differential diagnosis of CD, grading CD ulcerations, and grading UC for MES, but with variable performance and limited reproducibility 29–33 . Specifically, the accuracy of ResNet predicting endoscopic remission was 72.02%, compared with 84.52% of InceptionV3, 73.81% of VGG19, and 87.50% of DenseNet, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…ResNet, a more frequently used CNN architecture in IBD, has been used for differential diagnosis of CD, grading CD ulcerations, and grading UC for MES, but with variable performance and limited reproducibility. [29][30][31][32][33] Specifically, the accuracy of ResNet predicting endoscopic remission was 72.02%, compared with 84.52% of InceptionV3, 73.81% of VGG19, and 87.50% of DenseNet, respectively. To the best of our knowledge, although it has been the only study reported on the comparison of different CNN architectures in grading endoscopic images of UC so far, the limitations were marked with small samples, unsatisfactory performance, class imbalance among more moderate/severe cases, selection bias, and lack of multiclass classifcation.…”
Section: Mesmentioning
confidence: 97%
“…Although most clinical studies on lesion detection in endoscopic images have been conducted using the open-source AI algorithm, the excellent results are highly likely to be obtained only by a few Japanese companies that oliogopolize the gastrointestinal endoscopy market. Ruan et al have reported a high identification accuracy of a deep learning diagnostic system for inflammatory bowel disease ( 20 ). All endoscopic examinations were performed using an Olympus CV-290SL model.…”
Section: Discussionmentioning
confidence: 99%